Reflections on islamic Art - Soueif, Ahdaf (Doha (3OGQ HdheRHQj(B-(3eDSSI bWQ ddfTQ(B=Bloomsvury Qatar foundations, 2011)
from seventh-century Qur'ans hand writing to Art in exquisite carpets, remarkable portraits and items datin to the present day, the Museum of Islamic Art showcases one of the finest collections of Islamic Art in the world, including some of its rarest works. since its opening in 2008 the Museum. whic is housed in an iconic building designd by the celebrated I.M. Pei, has established itself as an outstanding contemporary expression of the islamic architectural tradition
"(3eJMa Gdaf GdESdGej (B= islamic Art museum"s
12
Keywords: Art and religion; Islamic art